ANALISIS PERMASALAHAN IMIGRAN GELAP DI KOTA PEKANBARU - Eddy Dame Parlindungan; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Presence of illegal immigrants in the Pekanbaru City is one problems that is very warm discussed among people in the Pekanbaru City and other sosial media both at local and national level. Presence of illegal immigrants in Pekanbaru City in background because of interfence or threaths both in terms of economic, political, social, security and so forth. Pekanbaru City the one of cities tath are part of Unitary State of Indonesian which lives on world trade and up holds human rigths especially those of the right to life. That is primary factor presence of illegal immigrants in Pekanbaru City. To overcome this problem the need for coordination and communication between policy, implementor and the environment in maintaining regional and state stabilitas. This research aims to look at the whole of illegal immigrants, government policy limiting factor in addressing the problems of immigrants in Pekanbaru City and also to see the impact that will occur the concept of theory Thomas R. Dye in William N. Dunn are three elements that make up a system policy. The third element of the policy is a public policy , stake holders and policy environment . This research using qualitative apporach using snowball sampling and data collection techniques with interviews, observation and documentation. These studies show that analysis of the issue of illegal immigrants in the city of Pekanbaru that most man for illegal immigrants to obtain protection in their country there is chaos in various fields. Inhibiting factor because this issue is handled directly by the central government and only if there is a problem regarding the coordination of these immigrants and their impact on the surrounding communities concerns such as the spread of the Shi'a and their followers spread of Islamic State Iraq and Syria (ISIS) is currently the talk warmer world. Keyword :Illegal of Imigrants, Problem